Interactions of digitalis and class-III antiarrhythmic drugs: Amiodarone versus dronedarone. (1st February 2017) - Frommeyer, Gerrit; Puckhaber, Dirk; Ellermann, Christian; Dechering, Dirk G.; Kochhäuser, Simon; Leitz, Patrick; Reinke, Florian; Eckardt, Lars
Abstract: Background: A post hoc analysis of the PALLAS trial suggested possible interactions of dronedarone and digitalis glycosides. The aim of the present study was to compare the effects dronedarone or amiodarone in combination with digitalis glycosides. Methods and results: Eleven female rabbits underwent chronic oral treatment with amiodarone (50 mg/kg/d for 6 weeks). Ten rabbits were treated with dronedarone (50 mg/kg/d for 6 weeks). Ten rabbits were used as controls. Hearts were isolated and Langendorff-perfused. Monophasic action potentials and ECG showed a moderate prolongation of QT interval and action potential duration (APD). Both drugs also increased effective refractory period. Additional application of ouabain (0.2 μM) resulted in a significant decrease of QT interval, APD, and ERP in all groups. Ventricular arrhythmias were induced by programmed ventricular stimulation and aggressive burst stimulation. Reproducible occurrence was defined as occurrence of at least 3 episodes. Under baseline conditions in control hearts, ventricular fibrillation (VF) was inducible in 1 of 10 hearts (7 episodes). After the application of 0.2 μM ouabain, 4 of 10 control hearts were inducible (24 episodes). One of 10 dronedarone-pretreated hearts (3 episodes) and 2 of 11 amiodarone-pretreated hearts (6 episodes) showed VF before ouabain infusion. After the application of 0.2 μM ouabain, 7 of 10 dronedarone-pretreated hearts were inducible (73 episodes). By contrast, only 4 of 11 amiodarone-pretreated hearts (13 episodes) showed VF. Conclusion: In the present study, additional treatment with ouabain resulted in an increased ventricular vulnerability in al study groups. Of note, chronically dronedarone-pretreated hearts were significantly more vulnerable than amiodarone-pretreated hearts.